Neoarchean reworking of Mesoarchean and Paleoarchean crust (3.4 ∼ 3.0 Ga) within the North China Craton: Constraints from zircon U-Pb geochronology and Lu-Hf isotopes from the basement of the Bohai Bay Basin - Meng, Fanchao; Tian, Yulu; Kerr, Andrew C.; Wang, Qianjun; Chen, Yong; Zhou, Yaoqi; Yang, Fei (Precambrian research, 2022)
•Zircon U-Pb ages establish magmatism at ∼ 3.1 Ga and ∼2.5 Ga in the basement of the Bohai Bay Basin (BBB).•Lu-Hf data establish Neoarchean crustal (∼2.5 Ga) reworking of Mesoarchean and Paleoarchean crust (3.4 ∼ 3.0 Ga) in the basement of BBB.•Continental crustal growth in the Eastern Block of the North China Craton was controlled by a mantle plume during the ∼2.5 Ga period. The Bohai Bay Basin basement is mainly composed of Archean granitoid gneisses with minor supracrustal rocks and is the largest basin in the Eastern Block of the North China Craton. Due to a cover of Mesozoic and Cenozoic strata, little is known about the age and crustal evolution of this basement. In this study we report new zircon SHRIMP and LA-ICP-MS U-Pb and Lu-Hf isotope data for drill core samples, including TTGs (granodiorite, tonalite gneiss, trondhjemite gneiss), granites (monzogranite, syenogranite) and a leptite, with the aim of revealing the Archean crustal evolutionary history of the Bohai Bay Basin basement. The U-Pb age of magmatic zircons from these granitoids reveals that basement rocks were mainly generated by two-stage events at ∼3.1 Ga and ∼2.5 Ga. The εHf(t) values of ∼3.1 Ga magmatic zircons vary from +0.56 to +8.27, and their corresponding single-stage model ages range from 3.3 Ga to 3.0 Ga. The εHf(t) values of ∼2.5 Ga magmatic zircons range from −12.87 to −0.07, their corresponding two-stage model ages range from 3.8 Ga to 2.9 Ga with most ages from 3.4 Ga to 3.0 Ga. The Hf isotopic characteristics show that the crustal growth of basement beneath Bohai Bay Basin occurred mainly between 3.4 Ga and 3.0 Ga, different from crustal accretion ages of 2.9–2.7 Ga on the periphery of the Bohai Bay Basin. However, both areas were reworked by the ∼2.5 Ga tectono-thermal event. Integration of this new data from the basin basement with previous data, indicates that the Eastern Block of the North China Craton may be controlled by a mantle plume during the ∼2.5 Ga period. The results from this study are significant in assessing the tectonic environment of the eastern basement in the North China Craton.